Partially replacing baleage with grazed forage canola in a component feeding system: Effects on production performance, enteric methane emissions, and nutrient utilization in dairy cows - L.H.P. Silva; Y. Zang; S.L. Dillard; K.J. Soder; A.F. Brito (Animal)
Forage canola is an annual crop with the potential to extend the grazing season and reduce enteric CH4 emissions due to its low fiber concentration. We aimed to evaluate the effect of partially replacing alfalfa-grass mix baleage with grazed forage canola on production performance, ruminal fermentation, enteric CH4 emissions, and nutrient utilization in dairy cows. Twelve multiparous Jersey cows averaging 131 ± 63 days in milk (DIM) and 462 ± 26 kg of BW and 6 primiparous Jersey cows averaging 175 ± 64 DIM and 418 ± 38 kg of BW were used in a randomized complete block design study. Treatments were formulated (DM basis) as follows: (1) 60% alfalfa-grass mix baleage, 38% concentrate pellet, and 2% roasted soybean (control = CON), and (2) 30% alfalfa-grass mix baleage, 30% grazed forage canola, 38% concentrate pellet, and 2% roasted soybean (forage canola = CAN). Cows in the CAN treatment had access to the forage canola pasture after the afternoon milking. The experiment consisted of a 2-week covariate period and a 5-week experimental period with samples collected during weeks 3 and 5. Although DM intake was greater in cows fed CAN than CON, milk yield was lowest in CAN. Milk true protein concentration, milk lactose yield, feed efficiency (milk yield/DM intake), milk N efficiency (milk N yield/N intake), ruminal pH and molar proportion of propionate, milk proportion of n-6 fatty acids, and enteric CH4 emissions were all lower in CAN versus CON. Treatment−by−week interactions were observed for the concentrations of milk urea N, plasma urea N, and ruminal NH3-N, apparent total-tract digestibilities of DM and organic matter, urinary excretion of urea N (g/day and % of urinary N excretion), ruminal molar proportion of butyrate, and milk proportion of n-3 fatty acids. For all these interactions, values were greater in CAN versus CON, but the magnitude of treatment differences varied from week 3 to week 5. A treatment by week interaction was also detected for the ruminal molar proportion of acetate, which decreased more pronouncedly in CAN than CON diet from week 3 to week 5. Intake of digestible energy and metabolizable energy (ME), and the efficiency of converting digestible energy into ME were greater in CAN than CON. Contrarily, the efficiency of converting ME into milk energy was lower in CAN versus CON cows. In brief, greater ME intake and nutrient digestibility in CAN compared with CON did not improve milk yield.